The Encyclopedia of Child and Adolescent Development 2020
DOI: 10.1002/9781119171492.wecad133
|View full text |Cite
|
Sign up to set email alerts
|

Early Understanding of Number

Abstract: We see, hear, and use numbers to communicate with other people on a daily basis. What are the origins of the human capacity for representing number? How does this capacity for number representation develop? To shed light on these questions, this entry reviews three types of evidence, from infancy till age 5: infants' abilities to process nonsymbolic quantities; children's protracted learning of the first few number word meanings; and how children may acquire a representation of number through learning the cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Average accuracy on counting-related questions was 73.8% (SD = 19.4%). The violin plot in Figure1also suggests that a majority of children performed well on counting-related questions, suggesting that at the average age of 4 years 9 months, most Singaporean children have learned how to count and use counting to identify the numerosity of collections, consistent with findings of previous studies from other countries (seeCheung & Ansari, 2020, for a review). Specifically, children understand the last word of a count refers to the total quantity of a collection of objects, and can use it to generate…”
supporting
confidence: 84%
See 2 more Smart Citations
“…Average accuracy on counting-related questions was 73.8% (SD = 19.4%). The violin plot in Figure1also suggests that a majority of children performed well on counting-related questions, suggesting that at the average age of 4 years 9 months, most Singaporean children have learned how to count and use counting to identify the numerosity of collections, consistent with findings of previous studies from other countries (seeCheung & Ansari, 2020, for a review). Specifically, children understand the last word of a count refers to the total quantity of a collection of objects, and can use it to generate…”
supporting
confidence: 84%
“…To learn counting, children learn to use a list of number words in a stable order (e.g., "one, two, three, four" and not "one, two, three, five") and assigning one number word to each object (Frye, Braisby, Lowe, Maroudas, & Nicholls, 1989;Fuson, 1988;Gelman & Gallistel, 1978). In addition to these procedural rules, numerous studies have shown that children learn how to use counting to generate sets of objects at around ages 3 to 4 (for a review, see Cheung & Ansari, 2020). That is, they understand that the last word of a counted set represents the total number of objects in the set, and this is termed the cardinal principle ( Le Corre, Van de Walle, Brannon, & Carey, 2006;Sarnecka & Carey, 2008;Wynn, 1990Wynn, , 1992.…”
Section: Arithmetic Abilities In Preschoolersmentioning
confidence: 99%
See 1 more Smart Citation